2018
DOI: 10.1148/radiol.2018172979
|View full text |Cite
|
Sign up to set email alerts
|

High-Frame-Rate Contrast-enhanced US Particle Image Velocimetry in the Abdominal Aorta: First Human Results

Abstract: Purpose To study the feasibility of high-frame-rate (HFR) contrast material-enhanced (CE) ultrasound particle image velocimetry (PIV), or echo PIV, in the abdominal aorta. Materials and Methods Fifteen healthy participants (six men; median age, 23 years [age range, 18-34 years]; median body mass index, 20.3 kg/m [range, 17.3-24.9 kg/m]) underwent HFR CE US. US microbubbles were injected at incremental doses (0.25, 0.5, 0.75, and 1.5 mL), with each dose followed by US measurement to determine the optimal dosage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 14 publications
3
33
0
Order By: Relevance
“…High frame rate contrast enhanced ultrasonography was successfully performed in the abdominal aorta of healthy volunteers. Velocity field information could be determined using ePIV (with the optimization described in this study) which was very similar to 4D phase-contrast magnetic resonance imaging [23]. of 0.01 (a, b) and 0.06 (c, d)…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…High frame rate contrast enhanced ultrasonography was successfully performed in the abdominal aorta of healthy volunteers. Velocity field information could be determined using ePIV (with the optimization described in this study) which was very similar to 4D phase-contrast magnetic resonance imaging [23]. of 0.01 (a, b) and 0.06 (c, d)…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the volunteers underwent MRI phase contrast imaging and the detected flow was compared to the ePIV results. This part of the study is not further described here, but reported elsewhere [23].…”
Section: A Study Designmentioning
confidence: 99%
See 1 more Smart Citation
“…A novel medical-based flow study technique is ultrasound PIV. In vitro studies 8,9 , as well as first clinical studies 10,11 , show the wide applicability of this technique. Also, in vitro validation of ultrasound PIV in the presence of a stent was recently performed 12 .…”
Section: Introductionmentioning
confidence: 91%
“…55,61 Furthermore, ventricular filling is studied using four-dimensional flow MRI. 16 Ultrasound-based vector flow imaging and echoPIV are used to study flow in the ascending aorta, 22 the abdominal aorta, 17,63 and to study ventricular blood flow. 27,32 The latter is also reported in combination with optical PIV flow studies.…”
Section: Strengths and Limitations Of This Reviewmentioning
confidence: 99%